Exploring Vocational High School Students’ Perceptions of Picture Series in Learning Descriptive Texts - Romi, Audrey Ananda; Farid Noor Romadlon; Nurcahyo, Agung Dwi (Universitas PGRI Semarang, 2025)
The ability to write descriptive texts in English remains a challenge for many EFL learners, particularly at the secondary vocational level, where students often struggle with generating ideas, organizing content, and using accurate vocabulary. Visual media such as picture series can serve as effective learning aids by stimulating imagination, guiding idea development, and making writing tasks more engaging. This study explores students’ perceptions of using picture series to support descriptive text writing in an eleventh-grade vocational high school in Kudus, Indonesia. Employing a descriptive qualitative design, the study collected data through questionnaires and semi-structured interviews with 30 students. The findings reveal that the majority of students perceive picture series as helpful in clarifying the stages of writing, expanding vocabulary, and reducing difficulties in composing descriptive texts. Students also reported that picture series enhanced their motivation and made writing activities more enjoyable. However, some challenges were noted, including dependence on visual aids and limited opportunities to develop writing autonomy. Overall, the study concludes that picture series are perceived positively as an instructional medium, with potential to foster students’ writing skills when used strategically in classroom practice. The results suggest that EFL teachers should integrate picture-based tasks with guided writing activities to balance support and independence in learning.